PENGUATAN NILAI – NILAI KARAKTER SISWA MELALUI KEGIATAN EKSTRAKULIKULER HADRAH - Mu'arifatul Waroh; Kustiana Arisanti; Herwati Herwati (Ta`Limuna: Jurnal Pendidikan Islam, 2023)
Abstract: This study aims to determine what character values are developed through hadroh extracurricular activities. In addition, it is also to find out the role of hadrah extracurricular coach teachers in order to strengthen student character. The research method uses qualitative research which is descriptive of a phenomenon that occurs at the research location. The results of this study are that the character of students that can be developed through hadrah extracurriculars is religious, hard working and communicative character. Then the role of the hadrah coach teacher in strengthening student character includes planning goals and determining competencies that must be mastered, assessing student participation in hadrah activities, providing explanations as well as giving examples, and assessing students' cooperative attitudes. The novelty in this study are that strengthening the religious, hard work and communicative character of students is not only through intracurricular activities but also through religious extracurricular activities such as this hadrah extracurricular.